Tom and Jerry tales. Volume four [videorecording (DVD)] (Distributed by Warner Home Video, 2008)
Tom and Jerry plung from one outrageous situation after another - from Zen master Tom beset by noisy neighbor Jerry to mystical transformations, from encounters with a genie and two sore sorceresses to the splendidly silly adventures of Tom and Jerry.